Empirical Model for Calculating the Peak Discharge and The Time Delay of Flood of Synthetic Hydrograph Unit in Sumbawa - Soewarno, S; Kustaman, Kustaman (Universitas Muhammadiyah Surakarta, 1999)
This research was carried out in Sumbawa island, it aims to determine: 1) the value of Snyderâs CT and CP coefficient of the synthetic unit hydrograph; 2) the empirical model to estimate of CT and CP coefficient; 3) the empirical model to estimate the peak flow and time lag of synthetic unit hydrograph. Based on rainfall â runoff data, Snyderâs T and CP coefficient of the synthetic unit hydrograph can be derived by syntheti means. The empirical model of CT and CP coefficient can be estimated by using the stepwise method of the multiple regression models. Measurable characteristics of watershed, including watershed area (LDP), length of main river (PSU), slope of watershed (KIM), forest area (LHT), sawah area (LSW), tegal area (LTG), grass area (LRUM), and mean annual rainfall (CHJ) are used to estimate these model. The most appropriate model is selected from a statistical test. Result of analysis show that the model can be used to estimate of Snyderâs CT and CP coefficient. These model can be used to make the empirical model to estimate the peak flow and time lag of synthetic unit hydrograph of ungauged watershed in Sumbawa island.